Faktor Yang Mempengaruhi Volatilitas Return Saham di Indonesia: Perusahaan LQ45 - Qatrunnada, Zalfa Shafira (Politeknik Ganesha Medan, 2024)
This article is an empirical article with purpose of providing evidence regarding to factors influence volatility stock return such as dividend policy, leverage and investor sentiment. This study consists of 145 observation year-firm of LQ45 corporate on the Indonesia Stock Exchange for the 2017-2021 period as a research samples based on the purposive sampling method. This study also uses secondary data from company financial report and multiple linear regression analysis as an analytical tool. The result of analysis show that dividend policy doesn’t play a role in influencing stock returns volatility. While, leverage and investor sentiment can positively influence volatility stock returns. This research can be a guide for capital market investors in estimating stock return volatility by considering macroeconomic factors such as dividend policy and leverage as well as through investor sentiment.